Makoto Suzuki - Suzuki, Makoto (The Japan Architect)
Artículo teórico en el marco del grupo ArchiText. Contiene: Collage 1975 : Seven ideas for spaces. Idea I: Light and tactile sensation. Idea II: Bubble units. Idea III: Ground-in. Idea IV: Man-maku. Idea V: Box and bag. Idea VI: Solid space and soft space. Idea VII: Close-in enviroment.